Stability Analysis and Control of a Microgrid against Circulating Power between Parallel Inverters. (January 2019) - Issa, Walid; Al-naemi, Faris; Konstantopoulos, George; Sharkh, Sulieman; Abusara, Mohammad
Abstract: In grid-connected mode, the grid normally absorbs all the power generated by each inverter in a microgrid. Droop control-based microgrid power management employs the frequency as a wireless communication to determine the power outage. However, in the cases of grid loss, each inverter should receive, from a supervisory controller, new settings of the output power suitable to the microgrid load. Because of the supervisory controllers are slower than the droop control loops, this might produce unstable dynamics caused by the excess generated power circulating between the inverters if the microgrid load is low. This case degrades the microgrid stability leading the DC link voltage of each inverter to rise to trip point. In this paper, a PD voltage control loop is proposed to stabilize the system and minimize the circulating power so providing more time for the supervisory control to respond without tripping any inverter. A detailed small signal model is developed and stability analysis is performed to tune the controller's gain. Matlab/Simulink results validate the performance of the proposed controller.